Implementation of Farming Acvities to Increase Early Childhood Self-Confidence - Kurniawati, Hartin; Nurussa'adaturrahmah, Nurussa'adaturrahmah; Ekaputri, Najla Tahani; Maemunah, Imun; Jie, Lie; Wei, Zhang; Jixiong, Cai (International Journal of Educational Narratives, 2023)
Background. This approach can be used in the context of early childhood education to promote personal development. Purpose. The aim of this study was to explore the role of agriculture in developing self-esteem in childhood. The research used was a controlled group experiment designed with 15 children aged 4-5 years as the research sample. Method. Data collection was carried out by measuring the level of self-esteem and recording the frequency of participation in agriculture. Results. The results of the study show that there is a significant relationship between working in the fields and increasing self-esteem in early childhood. Children involved in agriculture have increased their self-esteem. Farming gives children the opportunity to gain confidence in their abilities, overcome obstacles and learn to be independent. In addition, controlling for factors such as age, gender, socioeconomic background, family support, and parental involvement also influence children's development. Older age, positive family support, and parental involvement in farming are positively related to children's self-esteem. Lastly, the use of agricultural activities can be a good idea in developing self-esteem in early childhood. Conclusion. The recommendation of this study is to consider integrating agriculture into early childhood education programs and involve parents as key partners in this activity.